Spotlight on brexpiprazole and its potential in the treatment of schizophrenia and as adjunctive therapy for the treatment of major depression - Bruijnzeel, Dawn (Drug Des Devel Ther, 2016)
Antipsychotic agents, utilized for the treatment of a range of psychiatric disorders, differ substantially in terms of their pharmacology and adverse effect profiles. Incomplete and variable efficacy, differences in safety–tolerability, and highly heterogeneous response across individuals prompt development of new agents. Brexpiprazole is one of the two most recently introduced antipsychotic agents approved for the treatment of schizophrenia and as an adjunct for treatment of major depressive disorder. Its pharmacology, clinical trial data, and efficacy and side effects in comparison with other antipsychotic agents are discussed. Brexpiprazole is a dopamine D-2 partial agonist with potent activity at the serotonin 5HT(1A) and 5HT(2A) and noradrenergic alpha-1B and alpha-2C receptors. Placebo-controlled clinical trials in persons with schizophrenia support its efficacy in treating psychosis and preventing relapse. Short-term clinical trials also support its efficacy as an adjunct to antidepressants in treating major depressive disorder in individuals inadequately responsive to antidepressant treatment alone. Adverse effects include akathisia, gastrointestinal side effects, and moderate weight gain. The recommended oral dose of brexpiprazole is 2–4 mg/day in schizophrenia and 2–3 mg/day as adjunctive treatment in major depression. It must be titrated up to its target dose over 1–2 weeks and is effective in once-daily dosing. How brexpiprazole’s unique pharmacological profile will translate into clinically meaningful differences from other antipsychotic agents is unclear. Its place in our antipsychotic armamentarium and potential role in the treatment of schizophrenia and major depressive disorder will be determined by additional clinical data and experience.